Utilizing pretty typology in local community participation in homestay development: a case study of homestay Parit Penghulu Sungai Rambai, Melaka - Obed, Gingerlla (2014)
Local participation is one of the main elements of success in communitybased tourism. Community is one of the actors that must actively participate in tourism development. This research is to evaluate the level of community participation in Homestay program. The tools used to measure for the community participation is the Pretty Typology Ladder of Participation. There are three levels of community participation in Pretty Typology with unique differences of characteristics: (1) non-participation is the lowest level in Pretty Typology where communities are being manipulated and tourism development is generally developed by a powerful group, (2) degree of tokenism in community participation or towards active participation is where people have the opportunity in decision making and preparation of the action plan. There are some degrees of local influence in the development process, and (3) degree of citizen participation or interactive participation is the highest level in Pretty Typology. In this level local community, have their own decision making power and full control over all the development without external influences. Homestay Kampung Parit Penghulu in Sg. Rambai, Melaka was established in 2006 and have been awarded as the best Homestay with “The Best Homestay” for four times due to the excellent services they provide. They also have been awarded as the Best Small and Medium Industry Award in 2012 for their outstanding achievement in product development. Every household in the village actively participate in Homestay program development as the head of villagers encourage every household registered under the official board for Homestay program. This study was conducted to evaluate the level of community participation of Homestay Parit Penghulu based on the characteristic of willingness to take risks in tourism development, decision making power, the chance to control tourism development and aim in tourism development. The findings of this research had shown that community participation in Kampung Parit Penghulu on the highest level of participation that is degree of citizen participation or interactive participation while only a group from a local tour guide on the lowest level where the level of participation is only through consultations. The outcome of this research is the generation of new indicators to encourage community participation in Homestay program to improve the local economy and self-confidence among communities.